Konstitusionalitas Fungsi dan Wewenang Wakil Presiden RI Setelah Amandemen UUD 1945 - Johannes Johny Koynja (Fakultas Hukum Universitas Mataram, 2015)
This article represent effort to reflect again how far the 1945 Constitution of the Republic of Indonesia have guaranteed constitutionality function and authority of Vice President of Republic of Indonesia as